존 롤즈(J. Rawls)의 전쟁과 핵무기에 대한 이론: 국제법적 의미를 중심으로 - 정태욱 (원광법학, 39(3), 2023)
이글은 롤즈의 국제적 정의론 가운데 전쟁 관련 이론 그리고 핵무기 관련 이론을 특히 국제법의 관점에서 살펴보고자 하였다. 롤즈의 전쟁 이론은 서구 전통의 정전론(just war theory)에 기초하고 있다. 현실주의(realism)를 배격하고 평화주의(pacifism)를 취하지 않는다. 롤즈의 전쟁 개시의 정의(jus ad bellum)는 방어전쟁을 인정하고 예외적으로 인도적 개입의 전쟁도 긍정한다. 롤즈는 국제 사회 구성원을 질서정연한 만민들(well-ordered peoples)와 무법 국가들(out-law states)을 구분하고, 전자에 대하여만 전쟁 개시의 권한을 인정한다. 또한 유엔과 같은 초국가적인 국제기구에 의한 전쟁이 아니라 개별 국가들의 단독의 혹은 집단적인 제재 전쟁을 기본으로 하고 있다. 롤즈는 전쟁 과정의 정의(jus in bello)에서도 전투원과 민간인의 구분, 인권 보호, 군사적 필요성(목적-수단 논법)에 대한 제한 등 전통적인 국제인도법의 원리들을 대체로 반영하고 있다. 그러나 롤즈는 최고의 비상상황의 경우 민간인에 대한 군사행동을 허용한다는 점에서 국제인도법과의 차이를 보이고 있다. 핵무기에 대하여 롤즈는 핵억지론을 긍정한다. 다만 질서정연한 만민들(well-ordered peoples)에게만 핵을 허용하고, 핵 사용에 대하여 인권적 기준을 제시하고 있다. 따라서 기존 국제사법재판소(ICJ)의 핵 허용론과는 다소 차이를 보인다. 또한 롤즈는 히로시마-나가사키 원폭 투하에 대하여 커다란 잘못이라고 평가하고 있다. 히로시마-나가사키 원폭 투하에 대하여 미국의 공식 입장은 전쟁을 조기에 종결하기 위한 정당한 조치였다는 것이다. 그러나 롤즈는 미국 정부의 논거들을 배격하고, 그 원폭투하는 이른바 ‘정치가 정신’의 실패의 대표적인 경우라고 말하고 있다. 이 글은 그러한 롤즈의 관점을 국제인도법의 관점에서 뒷받침해 보고자 하였다. 히로시마-나가사키 원폭투하가 미군 장병의 희생을 줄이기 위한 것이라는 주장은 국제인도법의 군사적 필요성의 원리에 부합하지 않으며, 전쟁 장기화가 초래할 일본인 민간인 피해를 줄이는 불가피한 선택이었다는 주장도 다른 제3의 선택의 여지가 있었다는 점에서 타당하지 않다고 보았다. 히로시마-나가사키 원폭 투하는 무조건 항복이라는 미국의 정치적 승리 그리고 러시아(구 소련)의 참전 이전에 전쟁을 종결하고자 하였던 미국의 정치적 이해관계를 반영한 것일 뿐, 국제인도법의 군사적 필요성이나 인도적 필요성의 원칙에 부합하는 것은 아니었다고 보았다. This article tries to examine John Rawls’ theories of war and nuclear weapons especially from the perspective of international law. Rawls's theory of war is based on the just war theory of Western tradition. It rejects realism and does not adopt pacifism. Rawls's theory of jus ad bellum is similar to the position of current international law in that it recognizes a war of self-defense and exceptionally a war of humanitarian intervention. HIs theory of jus in bello largely reflects the principles of existing International Humanitarian Law(IHL), such as the distinction between combatants and civilians, protection of human rights, and restrictions on military necessity. However, Rawls deviates from international humanitarian law in that it permits military action against civilians in the case of the so-called supreme emergency. Regarding nuclear weapons, it differs from the existing International Court of Justice (ICJ) theory of nuclear permitting by permitting nuclear weapons only to well-ordered peoples and presenting human rights standards for nuclear use. In addition, by evaluating the Hiroshima-Nagasaki atomic bombings as great wrongs, it presents a precedent in international humanitarian law for the use of nuclear weapons. The official position of the United States regarding the Hiroshima-Nagasaki atomic bombings was that it was a justifiable measure to end the war early. However, Rawls rejects the U.S. government's arguments and says that the atomic bombing was a representative case of the failure of so-called 'statesmanship'. This article attempted to support Rawls's perspective from the perspective of international humanitarian law. The claim that the Hiroshima-Nagasaki atomic bombings were intended to reduce the casualties of U.S. soldiers does not comply with the principle of military necessity under international humanitarian law. Additionally, the claim that it was an inevitable choice to reduce the damage to Japanese civilians that would result from a prolonged war is not valid in that there was room for a third option to end the war. The dropping of the Hiroshima-Nagasaki atomic bombs reflected America's political interest for the victory of unconditional surrender and ending the war before Russia (the former Soviet Union) entered the war. This did not comply with the principles of military necessity or humanitarian necessity of international humanitarian law. KCI Citation Count: 0